Cat running - Snyder, Zilpha Keatley (New York, N.Y. : Bantam Doubleday Dell Books for Young Readers, 1994)
When eleven-year-old Cat Kinsey builds a secret hideout to escape her unhappy homelife, she slowly gets to know a poor family who have come to California after losing their Texas home to the dust storms of the 1930s.
Originally published: New York : Delacorte Press, 1994.
"A Yearling book."
Keywords: Depressions -- 1929 -- Fiction; Family life -- California -- Fiction; California -- Fiction; Depressions -- 1929 -- California -- Juvenile fiction